Personalized Learning for Indian Defence SMEs: A Study on Learner (Journal of Informatics Education and Research, 2025)
The rapid evolution of defence technologies necessitates continuous skill development within Indian Defence Small and Medium Enterprises (SMEs). Traditional learning models often fail to address SME employees’ diverse learning preferences, cognitive styles, and industry-specific skills requirements. This study explores the role of personalized learning in Indian Defence SMEs, focusing on learner preferences including language choices, duration preferences, knowledge standards, and VARK learning styles. A study was conducted in Hyderabad, encompassing three phases: initial data collection on demographics and learning preferences, adaptation of content to these preferences within a personalized learning management system (LMS), and subsequent evaluation through a survey completed by approximately 67 Defence SME employees. The results highlight significant variations in learning preferences and underscore the need for a customized e-learning framework. The findings indicate that AI-driven adaptive learning platforms may incorporate VARK-based training modules to optimize content delivery. Above highlight the importance of using multiple modes of information delivery to accommodate SME employees’ learning preferences effectively as one-size-fits-all approach may not be suitable.